2018
DOI: 10.1007/s00540-018-2531-7
|View full text |Cite
|
Sign up to set email alerts
|

Superior sealing effect of a three-dimensional printed modified supraglottic airway compared with the i-gel in a three-dimensional printed airway model

Abstract: The method of creating the mSGA that we proposed in this study can be applied to development of novel SGAs that is anatomically more suitable for pharyngolaryngeal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Four studies related to the development of customised devices to facilitate ventilation. 6164 These included a facial prosthetic to optimise mask fit in a patient with facial abnormalities and a silicone mask for a child with Trisomy 21, both constructed from 3D-printed negative moulds. 61 , 62 One study compared the use of an i-gel® (Intersurgical Ltd, Wokingham, Berkshire, UK) supraglottic airway with a 3D-printed modified version in 48 cadavers and found that there was a significant reduction in the force exerted on the airway mucosa and a significant increase in tidal volume during positive pressure ventilation with the printed device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies related to the development of customised devices to facilitate ventilation. 6164 These included a facial prosthetic to optimise mask fit in a patient with facial abnormalities and a silicone mask for a child with Trisomy 21, both constructed from 3D-printed negative moulds. 61 , 62 One study compared the use of an i-gel® (Intersurgical Ltd, Wokingham, Berkshire, UK) supraglottic airway with a 3D-printed modified version in 48 cadavers and found that there was a significant reduction in the force exerted on the airway mucosa and a significant increase in tidal volume during positive pressure ventilation with the printed device.…”
Section: Resultsmentioning
confidence: 99%
“…61 , 62 One study compared the use of an i-gel® (Intersurgical Ltd, Wokingham, Berkshire, UK) supraglottic airway with a 3D-printed modified version in 48 cadavers and found that there was a significant reduction in the force exerted on the airway mucosa and a significant increase in tidal volume during positive pressure ventilation with the printed device. 64…”
Section: Resultsmentioning
confidence: 99%
“…A recent study involving four medical students and two instructors examined and proved the usability of 3D-printed stethoscopes in auscultation training, in which they simulated mitral stenosis, mitral regurgitation, and aortic stenosis [ 24 ]. Supraglottic airway management devices have been successfully developed and tested on Thiel embalmed bodies [ 25 ]; however, no previous work has reported the use of 3D printing for manufacturing MAYO tubes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the microdevices processed by 3D printing technology have grown exponentially, demonstrating the great potential for cell biology, medical laboratory science, gene diagnosis [14,15]. Compared with traditional processing technology, 3D printing technology have incomparable flexibility and accuracy [16]. Several 3D printing materials have biocompatibility, which can meet the research and application needs of biological sciences and medicine [17].…”
Section: Introductionmentioning
confidence: 99%